All-PD control of pure Integrating Plus Time-Delay processes with gain and phase-margin specifications - Chakraborty S.; Ghosh S.; Naskar A.K. (My University, 2025)
It is well known that PD controller, though yields good servo response, fails to provide satisfactory regulatory response for Integrating Plus Time-Delay (IPTD) processes. On the other hand, using an integral control action generally leads to large overshoot or settling time. To achieve good servo as well as regulatory response, a new all-PD control structure is proposed for IPTD processes in this paper. Design formulas are derived in terms of gain-margin and phase-margin specifications. Numerical examples on the design methodology are presented and experimentally validated on a temperature control process. © 2017 ISA